Cannabinoid polymorphisms interact with plasma endocannabinoid levels to predict fear extinction learning. Issue 10 (20th June 2021) - Ney, Luke J; Matthews, Allison; Hsu, Chia‐Ming Ken; Zuj, Daniel V.; Nicholson, Emma; Steward, Trevor; Nichols, David; Graham, Bronwyn; Harrison, Ben; Bruno, Raimondo; Felmingham, Kim
Abstract: Background: The endocannabinoid system is gaining increasing attention as a favorable target for improving posttraumatic stress disorder (PTSD) treatments. Exposure therapy is the gold‐standard treatment for PTSD, and fear extinction learning is a key concept underlying successful exposure. Methods: This study examined the role of genetic endocannabinoid polymorphisms in a fear extinction paradigm with PTSD compared to healthy participants ( N = 220). Participants provided saliva for genotyping, completed a fear conditioning and extinction task, with blood samples taken before and after the task ( n = 57). Skin conductance was the outcome and was analyzed using mixed models. Results: Results for cannabinoid receptor type 1 polymorphisms suggested that minor alleles of rs2180619 and rs1049353 were associated with poorer extinction learning in PTSD participants. The minor allele of the fatty acid amide hydrolase (FAAH) polymorphism rs324420 was associated with worse extinction in PTSD participants. Subanalysis of healthy participants ( n = 57) showed the FAAH rs324420 genotype effect was dependent on plasma arachidonoyl ethanolamide (AEA) level, but not oleoylethanolamide or 2‐arachidonoyl glycerol. Specifically, higher but not lower AEA levels in conjunction with the minor allele of FAAH rs324420 were associated with better extinction learning. Conclusions: These findings provide translational evidence that cannabinoid receptor 1 and AEA are involved in extinction learning in humans. FAAH rs324420's effect on fear extinction is moderated by AEA plasma level in healthy controls. These findings imply that FAAH inhibitors may be effective for targeting anxiety in PTSD, but this effect needs to be explored further in clinical populations.